Anatomy of Dissent in Islamic Societies - Souaiaia, A. author. aut Link
XV, 228 p.
Keywords: Anatomy of Dissent in Islam is an interdisciplinary study of political and legal dissent in Islamic civilization from the seventh century on. (7th century). Using Ibadism as a case study, this work explores the events and teachings that shaped legitimacy and rebellion, orthodoxy and sectarianism, and law and culture in Islamic societies.